Mudslingers a true story of aerial firefighting (An American Origins Story) - Sheehy, Tim (New York, Nashville Permuted Press, 2023)
Blending historical context and first-person narrative, Mudslingers tells the dramatic and colorful story of aerial firefighting in America, as seen through the eyes of a decorated former Navy SEAL, US Naval Academy graduate, firefighting pilot, and businessman who founded Montana-based Bridger Aerospace, one of the most successful aerial firefighting teams in the world. Part narrative nonfiction, part memoir, Mudslingers is a riveting account of one person's journey from the battlefields of Afghanistan and Iraq to the front lines of a different but no less important battle on the home front--the war against the escalating threat of wildfire.From the early days of the B-17 to the modern fleets of the twenty-first century, Tim Sheehy will take you on a ride through the history of aerial firefighting--the most hazardous and demanding aviation mission in the world. Mudslingers is a rollicking read, an enlightening journey, and a call to action for anyone who believes wildfires are not only one of the greatest threats facing modern civilization but a threat that has long been underestimated, misunderstood, and poorly addressed, despite repeated examples of bravery and innovation by those who choose to do battle with the flames. Indeed, save for a few historic military engagements in the twentieth century, there is not a sustained aviation mission anywhere that comes close to encompassing the danger, precision, and unforgiving nature of aerial firefighting. In telling this story, Sheehy takes readers into the cockpit and into the lives of his fellow pilots--past and present--as they struggle with the seemingly never-ending threat of wildfires. One hundred percent of author proceeds from this book are donated to the Wildland Firefighter Foundation and the United Aerial Firefighters Association.
American Origins Stories - Prologue - American Mudslingers - Talk-Talk - The Road Less Traveled - The First Fire Bombers - Changing Lanes -Fighting Fire - Let if Burn - Flyboys - The Super Scooper - Accidents Will Happen - Airtankers - The Industrial Revolution - Withdrawal - Epilogue - Glossary --- Selected Bibliography & Sources - Acknowledgement.
Includes bibliographical references (pages 319-323) and index.
113653
Keywords: Wildfires -- Prevention and control; Wildfires -- Environmental aspects; Fire ecology; Wildfire risk; Wildfire fighters; Fire extinction -- Vocational guidance